Scots Pine Stems as Dynamic Sources of Monoterpene and Methanol Emissions - Vanhatalo, Anni; Aalto, Juho; Chan, Tommy; Hölttä, Teemu; Kolari, Pasi; Rissanen, Kaisa; Kabiri, Kourosh; Hellén, Heidi; Bäck, Jaana (Frontiers in Forests and Global Change, 2020)
The volatile organic compound (VOC) fluxes of living plant compartments other than foliage are poorly known. In this paper we describe for the first time the methanol and monoterpene fluxes from living Scots pine stems in situ, over four years at the SMEAR II station in southern Finland. The VOC fluxes from stems were measured online with an automated chamber measurement system. Both methanol and monoterpene emissions showed strong diurnal and seasonal cycles. Methanol emission rates were highest in mid-summer, and coincided with the most intensive period of stem radial growth. Methanol emission rates correlated moderately with the xylem sap flow rate and foliage transpiration rate, which suggests that many simultaneous and overlapping processes are related to methanol transport and production in trees. Monoterpene emissions from stems were highest on the hottest summer days, but also substantial in winter during times when the temperature was above zero °C for several days. Overall, the emissions from stems constitute about 2% of the whole stand monoterpene emissions under normal, non-stressed conditions. This can be used in stand monoterpene emission models as the rough estimate of woody compartment contribution.